Heat Transfer, Part B 2005
DOI: 10.1115/imece2005-80070
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement Effect of Corona Discharge on Natural Convection Heat Transfer in Triangular Channels

Abstract: A numerical research was conducted to investigate the effect of corona discharge on natural convection heat transfer in a triangular channel. The channel side walls were isothermal, the lower wall was adiabatic, and the fluid was air at the atmospheric pressure. The electric field was generated by a positive corona discharge from a charged wire electrode located at the center of the channel. The governing equations of the electric and flow fields were solved by a finite-volume technique. Three cases were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Their results showed that an increase in heat transfer depends on the number of electrodes and number of waves along the channel. Molki and Harirchian [16] numerically investigated the effect of corona discharge on natural convection heat transfer in a triangular channel. The results showed that the heat transfer was enhanced from 1 -4%, for different Ra values.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that an increase in heat transfer depends on the number of electrodes and number of waves along the channel. Molki and Harirchian [16] numerically investigated the effect of corona discharge on natural convection heat transfer in a triangular channel. The results showed that the heat transfer was enhanced from 1 -4%, for different Ra values.…”
Section: Introductionmentioning
confidence: 99%
“…A list of relevant studies using EHD in process engineering applications, dealing with heat transfer enhancement, is presented in Table 1. Many studies deal mainly with natural convection flow [19,21,31,32], and are rarely focused on the forced convection flow. Velkoff and Godfrey [16] reported the first experiments on heat transfer enhancement by ionic winds in the presence of external flows.…”
Section: Introductionmentioning
confidence: 99%